Does functional outcome depend on the quality of the fracture fixation? Mid to long term outcomes of ankle fractures at two university teaching hospitals. Issue 4 (August 2019) - Roberts, Veronica; Mason, Lyndon W.; Harrison, E.; Molloy, Andrew P.; Mangwani, Jitendra
Highlights: A large multicentre study looking at functional outcomes in reduced and malreduced ankle fractures. Medium to longterm outcomes. Pettrone score was inversely proportional to functional outcome. Abstract: Background: The aim of our study was to assess the adequacy of reduction and internal fixation of ankle fractures and the long-term functional outcomes of patients treated in two university teaching hospitals by general orthopaedic surgeons. Method: We performed a retrospective study involving two large trauma units in the UK, reviewing all operatively treated unstable ankle fractures performed in one centre between 1st October 2006 and 31st December 2007 and another centre between 1st January 2009 and 31st December 2009. All patients were contacted by postal follow up at a minimum of 6-years using the Olerud–Molander Ankle Score (OMAS). Results: 261 patients underwent operative treatment for ankle fractures during the study period at the two hospitals. 107 patients responded to the questionnaire. Analysis of patients' functional outcome by fracture type reveals that the outcome scores decrease as the complexity of the ankle fracture increases. A significant finding within subgroup analysis found that trimalleolar fractures (B3) have worse outcomes than bimalleolar fractures (B2 and C); which in turn have worse outcomes than isolated lateral malleolar fractures (B1). Analyzing the outcome of patients based on the severity of malreduction revealed that Pettrone's value was inversely proportional to the OMAS. Conclusion: We have found a significant reduction in patient reported function in patients whose fractures were malreduced at time of surgery.